IoT Security: Issues, Best Practices, and Open Challenges - Srikanta Kolay; Tryambak Hiwarkar (International Journal of Information Security Engineering, 2023)
The internet of things (IoT) provides the facility to connect different devices and communicate and share information over the internet. IoT has emerged as a transformative and pervasive technological paradigm, revolutionizing how we interact with our environment and infusing intelligence into everyday objects and devices. This interconnected ecosystem has unleashed a wave of innovative applications across diverse domains, including healthcare, transportation, agriculture, industrial automation, and smart cities. However, as the IoT footprint expands rapidly, it also brings to the forefront a multitude of complex and pressing security challenges that demand immediate attention and resolution. One of the primary security concerns in the IoT ecosystem is weak authentication and authorization mechanisms. Insufficient encryption measures can lead to data interception and manipulation, exposing confidential information to potential attackers. The lack of automated update mechanisms leaves numerous IoT devices susceptible to known exploits, necessitating the establishment of efficient update processes. With IoT devices deployed in the physical world, they become susceptible to tampering and theft, requiring robust physical security measures to safeguard their integrity. Standardization of security practices across the diverse IoT ecosystem is necessary to establish a unified and robust security framework. Security awareness and education are critical to empowering users and manufacturers to implement secure practices effectively. By comprehensively understanding and actively mitigating the key security issues, adopting best practices, and collaboratively addressing open challenges, we can forge a safer and more resilient IoT landscape that not only fosters innovation but also preserves user privacy and instills confidence in the trustworthiness of IoT technologies. This paper centers on addressing IoT security concerns and exploring the optimal practices to mitigate them. Finally, we point out open challenges as a scope of future research.
Keywords: Data Security; IOT Devices; Internet of things (IoT); IoT ecosystem; IoT security; data privacy; security challenge